Edukacyjne walory publicznych występów poznańskiej młodzieży szkolnej w XVI-XVIII wieku - Nowicki, Michał (Wydawnictwo Naukowe UAM, 2011)
It was characteristic for old Polish secondary education that all elements of school life were being used to enhance the impact of educational influence. According to the fact, that the basic program of teaching doesn't occupy children too much, they were able to prepare some public performances. We can distinguish a few examples: individual speeches, dialogues or theatre spectacles. These occupations were a great opportunity to exercise important skills for future public activity of young noblemen. Such kind of education was not only widely accepted by Polish society, but also suggested by some parents. Especially according to poetic and rhetoric education. One of the most important aims of that system was to create a human able to understand and create a popular culture. Thus public activities could be considered as a chance to develop skills of future politicians and, in general, members of society. But not only oratorical skills. We should remember, that such education was connected with some kind of knowledge and, what's more, moral values. Children during preparation to public performances were taught, for example, about the history of ancient civilizations and their culture, and the same with regard to Poland (including basic information about Polish modern offices or institutions). The most important aspect of these practices however was related to morality and civic education. Historical sources show us many examples: importance of religion in everyday life, justice, peace, concord and many other. These values were often personified and played by pupils in school theatre. It must be emphasized that these shows had a strong influence not only on a children education, but also on spectators. Already in 16th century it has been noticed that theatre or dialogues should be used in Poznań by Jesuits as a mean to teach people. This article concentrates on public performances in Poznań from sixteenth to eighteenth century. There were analyzed two secondary schools: Lubrański Academy and Poznań Jesuits College. The author wanted to show the similarity of educational system in these schools, the same involvement with preparing young people to public performances and the pedagogical aspects of this.
Educational values of public performanes of Poznań pupils from sixteenth to eighteenth centuryj
Keywords: Akademia Lubrańskiego; Kolegium Jezuickie w Poznaniu; historia wychowania; szkolnictwo średnie Poznania; Poznań; historia nowożytna; oświata staropolska; teatr szkolny; teatr staropolski; wychowanie; wartości wychowawcze; retoryka